ECOLOGIC APPROACH TO THE RESTORATION PROCESS AT AREAS DEGRADED BY MINING OPERATIONS - Kostenko, Victor; Zavialova, Olena; Chepak, Olga (My University, 2018)
Donetsk Region belongs to the zone of the most Ukrainian critical ones in provision with water and the quality of water. The main reason of the water quality deterioration is anthropogenic pollution due to untreated water discharge by the region’s industrial enterprises to water objects.
Keywords: Higher Aquatic Plants; Biological Purification; Geo-Thermal Power